Teachers’ Pedagogical Competence as a Determinant of Students’ Motivation Towards Business Education in Federal College of Education (Technical) Gombe in North-East Nigeria - I. Alhaji , Adamu,; H. Amin, Mohammed, (Kashere Journal of Education, 2021)
The aim of this study was to determine teachers’ pedagogical competence as a determinant of students’ motivation towards business education, the study adopted qualitative research and the design used for the study was instrumental case study. The participants were final year undergraduate business education students. The sampling technique used was purposeful sampling in selecting six (6) participants, three from the students and three from the academic staff. The researcher with the help of one (1) research assistant conducted face to face interview using semi structured interview protocol, with few open-ended questions. Data collected were analyzed using thematic analysis for interview. The results revealed that teacher’ pedagogical competences as a determinant of students’ motivation towards business education required possession of knowledge of the subject matter, use of appropriate teaching methods and using of instructional materials in teaching and learning process. The results also revealed that teachers’ pedagogical competence as a determinant of students’ motivation towards business education required teacher-student positive relationship, use of positive reinforcement and incentives, and teacher personality to motivate students towards business education. Based on the findings, it was recommended that Government, National Commission for Colleges of education, and other stakeholders should consider professional teaching qualification as pre-requisite for the recruitment of teachers and to provide in-service training, seminars, and conferences, workshops for the teachers, to improve in student-teacher relationship, and use of positive reinforcement/incentives in order to motivate students toward business education.